(untitled) (Research, Society and Development, 2021)
During the COVID-19 pandemic, the elderly (chronological age 65 years and above) are more susceptible to SARS-CoV-2 infection due to the altered immune system response and the higher rate of underlying comorbidities. The vast majority of mortalities are reported in elderly patients. Thus, this study aimed to evaluate some aspects related to the rehabilitation of COVID-19 in elderly patients and its interaction with multidisciplinary healthcare professionals. This is an integrative review with the aim of highlighting the importance of multidisciplinary care for the elderly in view of the conditions of COVID-19. The databases of scientific and technical literature consulted were: Latin American and Caribbean Literature on Health Sciences (LILACS); Google Scholar, Scientific Electronic Library Online (SciELO). The descriptors were selected based on the research objectives, namely: “COVID-19” and “Elderly”. Inclusion criteria were full articles published in the journal between January 2019 and May 2021 identified in June 2021. In total, 9 articles participated in this work. Among the main results obtained, the chance of involvement of various government agencies and various professions stands out. COVID-19 damages are more common in elderly patients, however, preventive, multidisciplinary and holistic assessments are essential to reduce the consequences of the disease. It is concluded in this work that the adoption of multidisciplinary care for health rehabilitation, together with the technical assistance of these professionals in prevention, represents a great impact on improving knowledge management, quality of care and safety for elderly patients.